2012
DOI: 10.1016/j.jacc.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for Discontinuation of Dual Antiplatelet Therapy

Abstract: E-ZES+3-month DAPT was noninferior to the standard therapy with respect to the occurrence of the primary endpoint. (REal Safety and Efficacy of a 3-month dual antiplatelet Therapy following E-ZES implantation [RESET]; NCT01145079).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 587 publications
(150 citation statements)
references
References 19 publications
0
148
0
2
Order By: Relevance
“…Figure 1 shows the study population (the study flow diagram is shown in fig A in the appendix). Six trials were included in the final analysis, comprising PROD-IGY, 25 OPTIMIZE, 26 EXCELLENT, 27 RESET, 28 SECU-RITY, 29 and ITALIC 30 (tables A-C in appendix). Among these randomised controlled trials, two studies compared 3 month with 12 month DAPT (RESET and OPTI-MIZE), two studies compared 6 month with 12 month DAPT (EXCELLENT and SECURITY), and two studies compared 6 month with 24 month DAPT (PRODIGY and ITALIC) (fig 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the study population (the study flow diagram is shown in fig A in the appendix). Six trials were included in the final analysis, comprising PROD-IGY, 25 OPTIMIZE, 26 EXCELLENT, 27 RESET, 28 SECU-RITY, 29 and ITALIC 30 (tables A-C in appendix). Among these randomised controlled trials, two studies compared 3 month with 12 month DAPT (RESET and OPTI-MIZE), two studies compared 6 month with 12 month DAPT (EXCELLENT and SECURITY), and two studies compared 6 month with 24 month DAPT (PRODIGY and ITALIC) (fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the four previously included randomised controlled trials, [24][25][26][27][28] we included the SECURITY 29 and the ITALIC 30 trials (fig 1 ; tables A-D in appendix). The intention to treat population was used for these analyses, including all patients according to randomised treatment arm regardless of actual treatment.…”
Section: Methodsmentioning
confidence: 99%
“…However, the greatest absolute reductions in cardiovascular events with dual antiplatelet therapy are seen in the first 3 months (table 1) and since these studies, advances in drug-eluting stent technology have led to a substantially reduced incidence of late (>30 days) and very late (>1 year) stent thrombosis. 16 In recent trials of patients treated with newer generation drug-eluting stents, shorter durations of dual antiplatelet therapy (3 months to 6 months) were non-inferior to 12 [17][18][19][20][21][22] months or 24 23 months of treatment with regard to etiher a composite of cardiovascular events or cardiovascular events plus major bleeding. Moreover, all of these trials included patients with an acute coronary syndrome (range 23% to 74% of study population) and in those who undertook prespecified subgroup analyses, no heterogeneity in treatment effect between stable and unstable coronary artery disease was observed (figure 3).…”
Section: Duration Of Dual Antiplatelet Therapy: Clinical Trialsmentioning
confidence: 99%
“…However some patient-related factors and device-related criteria that determine safety and allow early dual antiplatelet therapy withdrawal, or interruption e.g. for urgent surgery, still have to be determined [64,65]. It remains unclear whether there is a "safe" time threshold with the 2 nd generation DES, for clopidogrel discontinuation, after which event rates are negligible.…”
Section: ) Second Generation Des (Ees and Zes)mentioning
confidence: 99%